No Promoter Left Behind: Global Circadian Gene Expression in Cyanobacteria - Woelfle, Mark A. (2006)
Prokaryotic cyanobacteria express robust circadian (daily) rhythms under the control of a clock system that appears to be similar to those of eukaryotes in many ways. On the other hand, the KaiABC-based core cyanobacterial clockwork is clearly different from the transcription-translation feedback loop model of eukaryotic clocks in that the cyanobacterial clock system regulates gene expression patterns globally, and specific clock gene promoters are not essential in mediating the circadian feedback loop. A novel model, the oscilloid model, proposes that the KaiABC oscillator ultimately mediates rhythmic changes in the status of the cyanobacterial chromosome, and these topological changes underlie the global rhythms of transcription. The authors suggest that this model represents one of several possible modes of regulating gene expression by circadian clocks, even those of eukaryotes.